Tantangan Dan Peluang Dalam Perencanaan Pembelajaran Berbasis Teknologi - Aviva Hanum Siregar; Rahayu Rahayu; Safran Safran (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Technology-based learning has become a focal point in modern education, presenting both challenges and opportunities for educators. This study explores the dynamic landscape of planning pedagogy within the realm of technology-enhanced teaching. The research delves into the obstacles faced by educators when integrating technology into lesson planning, examining the associated opportunities for innovative pedagogical practices. Utilizing a qualitative approach, this study investigates the experiences of Aviva Hanum Siregar, Rahayu, and Safran, students in the PGMI program at the Faculty of Tarbiyah and Education Sciences, Universitas Islam Negeri Sumatera Utara. The findings highlight the diverse challenges encountered in adopting technology in lesson planning, such as technological barriers, resistance to change, and the need for continuous professional development. On the flip side, the study sheds light on the promising opportunities that arise from incorporating technology into teaching strategies. The authors discuss the potential for enhanced student engagement, personalized learning experiences, and the development of 21st-century skills. In conclusion, this research offers valuable insights into the multifaceted landscape of technology-based learning in the context of lesson planning. The identified challenges underscore the importance of strategic initiatives to address barriers, while the recognized opportunities point towards a transformative path for pedagogical innovation in higher education. Keywords: ,, -,,